Stress-Induced Increases in the Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - Zhang, J.H.; Li, M.; Han, F.; Yu X. Shi (Нейрофизиология, 2016)
We investigated the levels of expression of caspase-3 and 9 in the medial prefrontal cortex (mPFC) of rats subjected to single prolonged stress (SPS), trying to provide a novel insight into the mechanism of how this cortical region is related to post-traumatic stress disorder (PTSD). Fifty male Wistar rats were divided into the control group and four SPS groups examined at days 1,4,7, and 14 after treatment. Expression of caspase-3 in SPS groups was significantly greater when compared with the control group (P < 0.05) and peaked at day 7 after exposure to SPS. In the control group, the intensity of fluorescence of caspase-9- positive cells was low, while that in the SPS groups was significantly higher (P < 0.01) and peaked at day 4 after exposure to SPS. After SPS episodes, levels of mRNA of caspase-3 and caspase-9, compared with those in the control group, gradually increased and peaked at days 7 and 4, respectively (P < 0.01). Therefore, changes of expression of caspase-9 and caspase-3 may play an important role in the pathogenesis of PTSD.